P169 Don't whip it out until syphilis is ruled out. (23rd May 2012) - Teo, S Y; Fairley, I
Abstract : Introduction: Discrete syphilitic lesions mimicking testicular tumours are reported in the literature but usually diagnosed after removal of the testes in conjunction with positive syphilis serology. We present the first case, to our knowledge, in which a discrete testicular mass in the context of positive syphilis serology has been spared surgery and resolved both clinically and on serial ultrasound scans following antibiotic therapy. Case: A 47-year-old gentleman attended GUM clinic with inflammation under his foreskin and was found to have painless testicular lump on examination. Initial ultrasound revealed a 2 cm well defined, hypoechoic mass within the right testes. He was referred to urology on suspicion of malignancy. Subsequent Syphilis serology was positive and the penile lesion and testicular mass were felt to be consistent with syphilis. After liaising with the urology department, and in view of negative tumour markers (LDH, AFP and HCG) and known penicillin allergy, he was managed conservatively with doxycycline. Follow-up ultrasound scans at 1 month and 4 months revealed good resolution of the testicular mass. The last scan performed at 10 months after treatment revealed complete resolution. Conclusion: The case illustrates that syphilis needs to be considered in the differential diagnosis of testicular lumps and that conservative management with close follow-up can spare the patient radical orchidectomy.